Adsorption of Lead ions onto Activated Carbon derived from Sugarcane bagasse - Salihi, I.U. (Institute of Physics Publishing, 2017)
In this study, activated carbon was developed from sugarcane bagasse and its effectiveness in adsorbing lead (Pb2+) ions from synthetic aqueous solution was examined. Sugarcane bagasse activated carbon (SCBA) was developed in a tube furnace at a temperature of 900 °C, a heating rate of 10 °C/min, residence time of 3 hours, and at a nitrogen flow rate of 100 mL/min. Batch adsorption experiments were carried out to investigate the effects of pH and SCBA dosages on the adsorption process. The batch adsorption test showed that extent of Pb2+ adsorption by SCBA was dependent upon pH and SCBA dosage. The optimum pH for Pb2+ adsorption was found to be at pH 5.0. Maximum Pb2+ removal efficiency obtained from the batch studies was 87.3 at SCBA dosage of 10 g/L. Equilibrium adsorption data was described by Langmuir model with a coefficient of determination (R2) of 0.9508. Maximum adsorption capacity according to Langmuir model was evaluated to be 23.4 mg/g. The adsorption capacity of the SCBA was compared with that of other plant-based adsorbents. SCBA is an effective adsorbent for the removal of Pb2+ from aqueous solution. © Published under licence by IOP Publishing Ltd.